Pengembangan Buku Siswa Materi Jarak pada Ruang Dimensi Tiga Berbasis Science, Technology, Engineering, and Mathematics (STEM) Problem-Based Learning di Kelas X - Widya Nessa; Yusuf Hartono; Cecil Hiltrimartin (Jurnal Elemen, 2017)
This aim of this research is to produce a valid and practical teaching material on the matter 3-dimensional-space based Science, Technology, Engineering, and Mathematics (STEM) Problem-Based Learning and to know the potential effect from it. This research is qualitative with Design Research method. The subject in this research is 44 students form X MIA 4 SMA Negeri 19 Palembang. The stage of this research is preparation, formative evaluation consist of self evaluation, development, and field test. The data collection techniques are walktrough, documen, observation, and test. Based on this result, it has gained a valid teaching material on the matter 3-dimensional-space based Science, Technology, Engineering, and Mathematics (STEM) Problem-Based Learning in its content, construct, and language after passing the expert review and one-to-one stage. The practicabillity of this teaching material is looked from small group development stage. The potential effect from this teaching material is looked from the test result after learning process. The result of the test percentage is at 54% have reached the Minimal Complete Criteria. It shows that students’s book based STEM Problem-based Learning can be used in learning of distance in 3-Dimensional-Space lesson.